2010
DOI: 10.1007/s00264-010-1100-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased apelin serum levels and expression in human chondrocytes in osteoarthritic patients

Abstract: Apelin is a recently discovered hormone secreted by adipocytes. The aim of this study, therefore, was to evaluate the distribution of apelin in paired serum and synovial fluid (SF) of osteoarthritis (OA) patients, as compared to that in healthy controls, and to characterise the expression profile of apelin and its cognate receptor APJ in human chondrocytes. Apelin levels in serum and SF were analysed by enzyme-linked immunosorbent assay (ELISA). Expression of apelin and APJ in human chondrocytes was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
1
18
0
4
Order By: Relevance
“…Furthermore, apelin and APJ are expressed in osteoblasts where they may induce cell proliferation and promote survival (Xie et al 2006, 2007, Wattanachanya et al 2013; however, an increase in bone mass can be observed in apelin KO mice (Wattanachanya et al 2013). Recently, apelin has been reported to have a potential role in the pathophysiology of osteoarthritis (OA), as apelin is present in synovial fluid, and OA patients have elevated plasma apelin concentrations (Hu et al 2011). Blood plasma levels of apelin are reduced in patients with polycystic ovary syndrome (Chang et al 2011, Olszanecka-Glinianowicz et al 2012, consistent with the role played by apelin/APJ in metabolic disturbances such as insulin resistance.…”
Section: Other Functions Of the Apelinergic Systemmentioning
confidence: 99%
“…Furthermore, apelin and APJ are expressed in osteoblasts where they may induce cell proliferation and promote survival (Xie et al 2006, 2007, Wattanachanya et al 2013; however, an increase in bone mass can be observed in apelin KO mice (Wattanachanya et al 2013). Recently, apelin has been reported to have a potential role in the pathophysiology of osteoarthritis (OA), as apelin is present in synovial fluid, and OA patients have elevated plasma apelin concentrations (Hu et al 2011). Blood plasma levels of apelin are reduced in patients with polycystic ovary syndrome (Chang et al 2011, Olszanecka-Glinianowicz et al 2012, consistent with the role played by apelin/APJ in metabolic disturbances such as insulin resistance.…”
Section: Other Functions Of the Apelinergic Systemmentioning
confidence: 99%
“…Adipocytokines were recognised as modulators of the energy homeostasis, as well as an immunological, haemostatic and inflammatory processes [5]. Those substances also play an important role in the degradation processes of cartilage, bone and synovium [6]. Since their effect on the degenerative changes in non-loaded joints were demonstrated [7], they might provide a link between obesity and OA.…”
Section: Introductionmentioning
confidence: 99%
“…Some adipocytokines might also play a direct role in maintaining an inflammatory state in the joints of obese individuals (the so-called low-grade inflammatory state) [15]. These proteins have been detected in synovial fluid (SF) and the plasma of patients with OA [16][17][18]. A putative source of adipocytokine secretion in the region of the knee joint is the infrapatellar fat pad (IPFP) [19,20].…”
Section: Introductionmentioning
confidence: 99%